Metode Pembelajaran Al-Islam dan Kemuhammadiyahan di Universitas Muhammadiyah Sumatera Utara - Rasta Kurniawati Br. Pinem (UMSU, 2019)
Some problems that faced by the students in University of Muhammadiyah Sumatera Utara are have not disciplined in carrying out worship, have not well behaved in conveying their aspirations, some have not dressed in accordance with Islamic law, and there are only few alumni who become Muhammadiyah cadres whom automatically expected to be active in Muhammadiyah organization. There are several factors for these situation, including the learning method practiced by Al-Islam and Kemuhammadiyahan Lecturers (AIK) seemed monotonous and less interesting then the students feel bored to attend AIK lectures. The purpose of the study is to provide a learning method that fun and creative for AIK lecturers. In specific, the objective of the study is to detect and analyze the learning methods that have been applied by AIK lecturers in UMSU. The result after the observation has done, it was found that there were several learning methods practiced by AIK lecturers. All methods can be classified into three categories, classical, middle and modern methods.